Synthesis, structural, optical and dielectric characterization of Y1-xSrxCuO3 nanoceramics - Yalcin, Mesut; Ozmen, Denizhan; Takci, Deniz Kadir; Yakuphanoğlu, Fahrettin (Elsevier, 2022)
In the present study, Y1-xSrxCuO3 nanoceramics were synthesized in the form of ABO3 doped with different ratios of Sr (x = 0, 0.01, 0.05, 0.15 and 0.20) using yttrium and strontium in site A and copper in site B. The structural and morphological characteristics of the synthesized nanoceramics were examined with spectroscopy techniques. The dielectric constants and the optical band gap of the ceramics (Eg) were calculated. It was determined that the ceramics had a narrow direct transition optical band gap in the range of 1.59-1.68 eV. Y1-xSrxCuO3 nanoceramics were determined to have the potential for use in optoelectronic devices.
Keywords: Y 1-x Sr x CuO 3; Nanoceramic; Wemple-didomenico; Optical band gap; Dielectric constants